Brain-train apps: Testing the efficacy of two applications for cognitive enhancement - Vranić, Andrea; Popović Stijačić, Milica; Martinčević, Marina (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
With the ubiquitous trend of almost every individual in the world owning a smartphone, new trends have emerged within applied cognitive psychology regarding the use of applications for cognitive training purposes. Previous studies have found far-transfer benefits of training a single working memory component, such as gains in fluid abilities. We aimed to evaluate two smartphone applications - Dual n-back, Super Number Memory, tapping the central executive and phonological loop, respectively. Young adults (N=176, Mage =21.5, SD=5.42; 87% female) were randomly assigned to either one of the three experimental groups (Dual n-back app, Super Number Memory app, combination of the two apps), or to a control group. A pre-post design with FU at three months was employed, with a 4-week training (5 sessions a week). A near transfer effect for updating ability in young adults was confirmed for the Dual n-back and combined group, while no other effects were found. The results are discussed in terms of the efficacy of mobile phone apps for cognitive functions improvement.